Constructing a bifunctional MoO2/Co heterojunction for efficient electrocatalytic hydrogen evolution and hydrazine oxidation. Issue 33 (12th August 2022) - Guo, Yuhao; Liu, Xiaolei; Zang, Yanmei; Wu, Yaqiang; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Cheng, Hefeng; Huang, Baibiao; Dai, Ying; Wang, Peng
Abstract : A self-supporting MoO2 /Co heterojunction porous nanosheet array acts as a beneficial bifunctional electrocatalyst for an overall hydrazine splitting (OHzS) system. Abstract : The anode oxygen evolution reaction (OER) in electrochemical water splitting hinders the cathode hydrogen evolution reaction (HER) due to its larger thermodynamic barrier and slow kinetic process, while the anode hydrazine oxidation reaction (HzOR) provides an alternative way to solve this problem. Meanwhile, metal-based electrocatalysts frequently appear in cathodic reactions due to their excellent electrical conductivity and catalytic performance. However, the susceptibility to oxidation of metals limits their application in anodic reactions. Herein, we successfully introduced cobalt (Co) metal as a host material to synthesize the MoO2 /Co heterojunction for the electrocatalytic reaction, which can achieve a current density of 10 mA cm −2 at −48 mV for the HER and −73 mV for the HzOR. Moreover, the two-electrode overall hydrazine splitting (OHzS) electrolyzer requires an extremely small cell voltage of 35 mV for 10 mA cm −2 . DFT calculations demonstrate that MoO2 and Co can simultaneously optimize the free energy of hydrogen adsorption (Δ G H* ) and the stepwise dehydrogenation process of N2 H4 benefiting from the constructed heterojunction. This research designs an innovative method of developing metal-incorporated materials for the study of enhanced bifunctional electrocatalysts and improves an energy-efficient H2 generating technology.